Good morning, Miss Dove [videorecording (DVD)] - Koster, Henry, 1905-1988; Stack, Robert, 1919-2003; Hamilton, Kipp; Douglas, Robert, 1909-1999; Patton, Frances Gray (20th Century Fox cinema archives., 2014)
A hospitalized school teacher reviews her career through visits from her former students.